Personal transformations of the elements of behavioral component of law enforcement officers’ professional activity - N. Ye. Tverdokhliebova (Law and Safety)
The author of the article has provided the results of the study of the features of personal transformations of the elements of behavioral component of law enforcement officers’ professional activity at the stage of training in higher educational institutions with specific learning conditions. The interdependent elements of behavioral component of a law enforcement officer’s professional activity have been singled out, namely: the adaptive potential of an individual, skills and behavioral self-regulation styles, individual and business qualities, mechanisms of psychological protection and coping-behavior strategies.